Penggunaan Sensor Fr-04 Untuk Atap Jemuran - Umar, Nuraeni; Yuniarti, Yuniarti; Kato, Franklin Aditama; Gunawan R, Riyan (Jurnal Teknologi Elekterika, 2023)
The FR-04 sensor is used on a clothesline roof, the research aims to overcome problems with clothesline when it rains it gets wet. This system functions to prevent the clothesline from getting wet by rain. This system moves to close and open the clothesline roof. The clothesline roof system will move to open or cover the clothesline, according to the input conditions of the light sensor (LDR) and rain sensor. The FR-04 sensor detects the presence of water droplets on the surface, then the Servo (as the driving force for the clothesline) will rotate 1800 Clockwise (clockwise and buzzer on. The results of the FR-04 Sensor system functioned very well to detect the presence of water droplets on the surface, and the system managed to close and open the clothesline roof by rotating 1800.Â